A Multi-Method and Structure-Based In Silico Vaccine Designing Against Helicobacter pylori Employing Immuno-Informatics Approach - Naz, Anam; Zaheer, Tahreem; Dar, Hamza A.; Awan, Faryal Mehwish; Obaid, Ayesha; Ashraf, Shifa Tariq; Paracha, Rehan Zafar; Malik, Arif; Ali, Amjad (Current Proteomics, 2021)
Background: Helicobacter pylori infection and its treatment still remain a challenge for human health worldwide. A variety of antibiotics and combination therapies are currently used to treat H. pylori induced ulcers and carcinoma; however, no effective treatment is available to eliminate the pathogen from the body. Additionally, antibiotic resistance is also one of the main reasons for prolonged and persistent infection. Aims: Until new drugs are available for this infection, vaccinology seems the only alternative opportunity to exploit against H. pylori induced diseases. Methods: Multiple epitopes prioritized in our previous study have been tested for their possible antigenic combinations, resulting in 169-mer and 183-mer peptide vaccines containing the amino acid sequences of 3 and 4 epitopes respectively, along with adjuvant (Cholera Toxin Subunit B adjuvant at 5’ end) and linkers (GPGPG and EAAAK). Results: Poly-epitope proteins proposed as potential vaccine candidates against H. pylori include SabA-HP0289-Omp16-VacA (SHOV), VacA-Omp16-HP0289-FecA (VOHF), VacA-Omp16-HP0289- SabA (VOHS), VacA-Omp16-HP0289-BabA (VOHB), VacA-Omp16-HP0289-SabA-FecA (VOHSF), VacA-Omp16-HP0289-SabA-BabA (VOHSB) and VacA-Omp16-HP0289-BabA-SabA (VOHBS). Structures of these poly-epitope peptide vaccines have been modeled and checked for their affinity with HLA alleles and receptors. These proposed poly-epitope vaccine candidates bind efficiently with A2, A3, B7 and DR1 superfamilies of HLA alleles. They can also form stable and significant interactions with Toll-like receptor 2 and Toll-like receptor 4. Conclusion: Results suggest that these multi-epitopic vaccines can elicit a significant immune response against H. pylori and can be tested further for efficient vaccine development.
Keywords: poly-epitope peptide vaccine